A Scoping Review The Relationship Between Anemia in Pregnant Women and the Incidence of Low Birth Weight (LBW): HUBUNGAN ANEMIA PADA IBU HAMIL DENGAN KEJADIAN BERAT BAYI LAHIR RENDAH (BBLR) - Shofa Rosyida; Nadifah Audina P; Almira Sitasari; Tri Siswati; Agus Wijanarka (Media Gizi Mikro Indonesia, 2026)
Background: Anemia is a health problem that occurs in many developing countries, especially Indonesia. Anemia in pregnant women or gestational anemia is a public health problem that occurs a lot. Pregnant women with anemia are at high risk of giving birth to babies with low birth weight. Objective: To see how the assessment of anemia in pregnant women is enforced and to see if there is a relationship between pregnant women who suffer from anemia and the incidence of low birth weight. Methods: The method used was the identification of literature published from 2020 to 2024. The literature was searched using databases such as PubMed and Google Scholar. The terms used in the search were: pregnant women, anemia, and low birth weight. The results of the literature obtained were then included in the inclusion and exclusion criteria until 10 pieces of literature were obtained. The inclusion criteria were that the literature was researched or published in the range of 2020-2024, observational research design, there were criteria for measuring anemia, could answer the research question, and the results were whether or not there was an association between anemia in pregnant women and the incidence of low birth weight. While the exclusion criteria are incomplete literature, not observational research, literature does not discuss the relationship between anemia in pregnant women and the incidence of low birth weight. Results: In 7 journals that prove a significant relationship between anemia pregnant women and the incidence of LBW or low birth weight of babies under 2500 grams. However, there are 3 journals that oppose this statement stating that there is no significant relationship between anemia in pregnant women and the incidence of LBW and the normal group has a higher risk of giving birth to premature and LBW babies than the gestational anemia and non-anemia iron deficiency groups. Conclusion: This study explains the significant relationship between anemia in pregnant women and the incidence of LBW. Anemia during pregnancy is a contributing factor to LBW as evidenced by the existence of 7 relevant literature out of 10 identified literature. ABSTRAK Latar Belakang: Anemia pada ibu hamil masih menjadi masalah kesehatan masyarakat, terutama di negara berpendapatan rendah dan menengah, termasuk Indonesia. Penurunan kadar hemoglobin selama kehamilan dapat mengganggu suplai oksigen ke janin sehingga meningkatkan risiko BBLR. Namun, bukti mengenai hubungan antara anemia pada ibu hamil dan kejadian BBLR belum konsisten. Tujuan: Mensintesis bukti ilmiah mengenai hubungan antara anemia pada ibu hamil dan BBLR, serta mendeskripsikan metode yang digunakan untuk menilai anemia pada ibu hamil. Metode: Penelitian ini menggunakan pendekatan scoping review yang mengacu pada pedoman Joanna Briggs Institute (JBI) dan dilaporkan sesuai PRISMA-ScR. Penelusuran literatur dilakukan melalui basis data PubMed dan Google Scholar terhadap artikel yang diterbitkan pada tahun 2020–2024, dengan kata kunci pregnant women, anemia, dan low birth weight.  Setelah melalui proses seleksi berdasarkan kriteria inklusi dan eksklusi, diperoleh sepuluh artikel yang dianalisis. Hasil: Tujuh dari sepuluh studi melaporkan adanya hubungan yang signifikan antara anemia pada ibu hamil dan peningkatan risiko BBLR. Sebagian besar penelitian mendefinisikan anemia berdasarkan kadar hemoglobin <11 g/dL dan mengidentifikasinya sebagai faktor risiko penting terhadap BBLR. Sementara itu, tiga studi tidak menemukan hubungan yang bermakna secara statistik, yang kemungkinan dipengaruhi oleh perbedaan metode penilaian anemia, desain penelitian, status gizi ibu, serta faktor perancu lainnya. Kesimpulan: Bukti yang tersedia menunjukkan bahwa anemia pada ibu hamil merupakan salah satu determinan penting kejadian BBLR. Namun, kekuatan hubungan tersebut masih bervariasi akibat perbedaan metodologi penelitian dan sifat multifaktorial BBLR. Untuk itu, diperlukan standardisasi penilaian anemia serta penelitian prospektif dengan rancangan yang lebih kuat untuk memperkuat bukti ilmiah dan mendukung intervensi kesehatan ibu yang lebih efektif.